PENAFSIRAN KONTEKSTUAL AYAT AYAT TARBAWI (PENDEKATAN ASBABUN NUZUL) - Fatoni, Muhamad; Amrullah, Ahmad Fikri (IAIN Tulungagung, 2019)
This article discusses the verses of the Qur'an which has asbabun nuzul containing educational values. By using a content analysis approach, the researcher seeks to unravel the messages that are present in the tarbawiyah verses, and to contextualize the development of the times as the nowadays implementation. There are at least eight verses of tarbawiyah which has asbabun nuzul. From the eight verses the author classifies them in three topics, namely the spirit of education, educators, students and Islamic education material. Keywords: tarbiyah verses, asbabun nuzul, education